2017
DOI: 10.12659/msm.902193
|View full text |Cite
|
Sign up to set email alerts
|

Expression of High-Mobility Group Box 1 Protein (HMGB1) and Toll-Like Receptor 9 (TLR9) in Retinas of Diabetic Rats

Abstract: BackgroundDiabetic retinopathy (DR) and diabetic optic neuropathy are important complications of diabetes mellitus (DM) which can lead to blindness in diabetic patients. Recent studies showed that chronic low-grade inflammation is thought to be one of the important pathophysiological mechanisms in the occurrence and development of DR and diabetes optic neuropathy. This study explored the expressions of inflammatory factors HMGB-1 and TLR9.Material/MethodsSD rats were randomly divided into a diabetic mellitus g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…It may exert its function via the TLR-9 pathway. The expression of TLR-9 was increased and positively related to the expression of HMGB1 [75].…”
Section: Hmgb1 and Drmentioning
confidence: 91%
“…It may exert its function via the TLR-9 pathway. The expression of TLR-9 was increased and positively related to the expression of HMGB1 [75].…”
Section: Hmgb1 and Drmentioning
confidence: 91%
“…TLR9 is a cytosolic receptor bound to the membranes of intracellular organelles (e.g., endosomes, lysosomes, and endolysosomes) and is responsible for identification of unmethylated cytosine-phosphate-guanosine DNA present in bacteria and viruses [ 211 , 254 , 255 ]. Furthermore, TLR9 has been shown to directly contribute to cardiac, hepatic, and renal ischemic tissue injury [ 211 ] and lupus nephritis [ 256 , 257 ] through recognition of endogenous mitochondrial DNA products [ 258 ], chromatin IgG complex [ 259 ], GP96 [ 260 ], high-mobility group box-1 [ 261 ], and heat-shock protein 90 [ 262 ]. A study involving CIAKI determined a protective immunomodulating role of TLR9 in disease progression, as TLR9 absence resulted in accelerated and increased pathological development [ 56 ].…”
Section: Cisplatin-induced Acute Kidney Injury: Role Of the Immunementioning
confidence: 99%
“…Levels of HMGB1 are increased in retinas of diabetic rats [123,124] and in patients with proliferative diabetic retinopathy (PDR) [125,126], together with endothelial activity biomarkers like ICAM-1, sICAM-1, MCP-1, VEGF, Granulocyte-colony stimulating factor (G -CSF), sVE-cadherin and soluble endoglin (sEng), supporting the contribution of HMGB1 in neovascularization process [123,[125][126][127][128][129]. Moreover, El-Asrar and coworkers demonstrated that levels of HMGB1 are higher in patients with PDR and retinal hemorrhages, suggesting a role of the protein in PDR progression [126].…”
Section: Hmgb1 and Diabetic Retinopathymentioning
confidence: 99%